Penerapan Permainan Tradisional Untuk Meningkatkan Motivasi dalam Pembelajaran PJOK Kelas XI-3 SMAN 1 Gedangan Sidoarjo - Mohammad Nashir; Sasminta Christina Yuli Hartati; Supriyono Supriyono (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This study focuses on the low learning motivation among students in class XI-3 at SMAN 1 Gedangan. The aim of this research is to gather information and investigate the effect of implementing traditional games to enhance motivation in PJOK learning for class XI-3 at SMAN 1 Gedangan, Sidoarjo. The stages of planning, implementation, observation, and reflection of the action research project were followed in this study. Thirty-six students from class XI-3 at SMAN 1 Gedangan participated in this research. The researcher used a questionnaire that was distributed during a pre-test before the treatment and a post-test after the treatment to draw conclusions. Data were analyzed using SPSS 25 with five formulas applied: mean, standard deviation, variance, normality test (chi-square), and percentage increase. Based on the data analysis conducted, it was found that the implementation of traditional games has an effect on students' learning motivation in Physical Education, Sports, and Health in class XI-3. This is evidenced by the analysis results showing a sig value of 0.00, which is less than 0.05, leading to the rejection of H0 and acceptance of Ha. The effect size of implementing traditional games in enhancing learning motivation is 30%.